Developing a Technology Implementation Framework from the Perspective of Sustainability - Zakaria, Sharifah Akmam Syed; Rahim, Nur Soleha Abdul (School of Social Sciences, USM, 2017)
Consideration of sustainability elements during the decision-making process in a construction project requires knowledge and awareness on the issues affecting environmental, social and economic aspect. Malaysia’s construction agencies have highlighted the important of environmental sustainability in the Construction Industry Transformation Programme (CITP) as a guideline in achieving a more sustainable construction. Every year, gigantic amount of solid wastes are generated from construction industry which create multiple environmental issues and causing pressure to the disposal sites. Implementation of information technology such as building information modelling (BIM) is considered as one of the alternatives in resolving the construction issues. The capability of BIM in predicting potential waste generation, avoid increases in project’s cost and producing a better quality of end products indirectly contributing to the improvement of construction industry’s image. However, there is still lack of BIM implementation among construction players in Malaysia. As the first step in exploring technology implementation in the construction industry, the development of proper framework is needed to identify the potential numbers of companies having the capability to drive the implementation. In order to validate the proposed technology implementation framework, an analysis related to student’s sustainable dailylife activities was conducted. A total number of 155 students from a local university in Malaysia were involved in the survey. The results indicate that currently students are still requiring information to increase awareness on the daily-life activities that can contribute to sustainability. In academic institutions, practicing sustainable life would increase student’s awareness on the impact of simple dailylife activity towards the physical environment of the planet. This attitude should be maintained by each student and the sustainable life shall be practiced continuously particularly when the students are venturing into the real working environment. Thereby, young engineers will appreciate the nature further and develop a more sustainable development for future generations.